Concerns and Considerations: Creutzfeldt-Jakob Disease in Pakistan and Reusable Laryngoscopes - Maheen Ahmed; Misha Ahmed (Journal of the Pakistan Medical Association)
The world witnessed a transition to single-use laryngoscopes from reusable laryngoscopes with the rise of Creutzfeldt-Jakob disease (CJD). Hill et al. found CJD in tonsillar tissue. (1) Another study reported laryngoscope blades contaminated with lymphocytes after routine laryngoscopy. (2) It is known that prions resist conventional sterilisation techniques. This raises the concern that if a laryngoscope is used on a patient incubating CJD, we could transmit it to the next patient.